Efficacy of plant extracts in the suppression of insect pests and their effect on the yield of sunflower crop under different climatic conditions (The Journal of Plant Protection Sciences, 2020)
A B S T R A C TSunflower (Helianthus annuus L.) is an annual herb scarcely cultivated in Bangladesh. During cultivation, the coccinellid beetle, Epilachna varivestis (Coleoptera: Coccinellidae) severely attacked the foliages and florets in the capitulum (inflorescence). Other pests encountered were Spilosoma obliqua (Walker) (Lepidoptera: Arctiidae), Homoeosoma • (Lepidoptera:    Keywords: Plants extracts, insectpests, sunflower Bangladesh, botanical insecticides. Phyticidae), Heliothis armigera (Hb.) (Lepidoptera: Noctuidae), Monolepta signata (Oliv.) (Coleoptera: Chrysomelidae) and Epilachna septima Dieke. (Coleoptera: Coccinellidae) . The efficacy of five kinds of plant extracts or botanicals viz., Neem (Azadirachta indica) seed oil, castor (Ricinus communis) oil, a mixture of Neem seed oil and sesame oil, leaf extracts of custard apple (Annona squamosa) and Bara Bishkatali (Polygonum orientale) were tested against the pest infestation. The treatment of custard apple leaf extract produced the most favourable result in respect of pest control and crop yield. The other treatments also exhibited better results in comparison to control followed by Bara Bishkatali, Neem seed oil, a mixture of Neem seed oil and sesame oil, and castor oil. The yield was 10.8 and 12.0 maunds per acre in the crop fields of Lalmonirhat and Rajshahi Oilseed cultivation Centres, respectively.
Keywords: Plant extracts; insect pests; sunflower; Bangladesh; botanical insecticides